PENERAPAN STRATEGI POLITENESS BROWN DAN LEVINSON DALAM KONFLIK CERPEN PERSIMPANGAN KARYA RADITYA DIKA - Nensilianti Nensilianti; Ridwan; Nurhidayah Aprilia Nuna nk (Universitas Islam Zainul Hasan Genggong, 2026)
This study explores the politeness methods described by Brown and Levinson (1987) in dealing with emotional conflict in the short story